If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(4x-2=-2(3+6x
We move all terms to the left:
-5(4x-2-(-2(3+6x)=0
We add all the numbers together, and all the variables
-5(4x-2-(-2(6x+3)=0
| 2.30+0.60x=27.3-0.40x | | -5×y/3+3=8 | | x/5+3x/4=19 | | 5+3/4x=x-6 | | 4(1+6p)−8=−148 | | 2.9+10m=8.72 | | t3− 13=–10 | | 11x-26=x-4x-16+9x | | -8.5x=17 | | 5(x-)-8=22 | | 3x=24-2 | | 4x^2-17x-10=5 | | 30-2t=4t | | 5x–9=4x+7+x | | -46=-4+3m | | 7x+28=8x+2) | | ?x15=105 | | -12=2-5x=7 | | 4=x^2-6 | | -(3x-3)-(2x-5)+4=-5(x1)-(3x+2)+3 | | -11+11n=-121 | | 25=r+2+2r-13 | | X+5=2x-24=180 | | 7=-3+2a | | 2(3x-4)=-8-6x) | | 4.3x-7.95=2.8 | | -(8m+8)=-16 | | -5y÷3+3=8 | | 2/3(3x+9)=−2(2x+6) | | 5h-4h+3h-4h+2h=12 | | 7x-5(x-4)=18 | | y=-54 |